Congenital lupus erythematosus - Taseer Ahmed Bhatt; Hanadi A Fatani; Samara Mimesh (Wolters Kluwer Medknow Publications, 2011)
Neonatal lupus erythematosus (NLE) is an autoimmune disease affecting the fetus as a result of transplacental transfer of anti-Ro autoantibodies. Typically, it presents in the first few months of life with an annular form of subacute cutaneous lupus erythematosus. We report an unusual case of NLE presenting at birth with scaly erythematous telangiectatic patches and macules with skin atrophy involving the face, head, and upper trunk. Thrombocytopenia was discovered on laboratory investigations. Histopathology of skin biopsy was consistent with subacute cutaneous lupus. The mother was clinically free of disease and had no family history of autoimmune disease. Serology (extra-nuclear antigens) was positive in both the baby and the mother. This is a rare presentation of a rare disease.